How Do Adult Survivors of Childhood Sexual Abuse Experience Formally Delivered Talking Therapy? A Systematic Review. Issue 7 (2nd October 2016) - Parry, Sarah; Simpson, Jane
ABSTRACT: This systematic review explored how adult survivors of child sexual abuse experienced nonspecific and trauma-focused talking therapies. Following extensive systematic searches of academic databases, 23 qualitative empirical studies were chosen for review. Using a line-by-line thematic synthesis, four analytical themes developed. These themes were: The Therapeutic Process as a Means for Forming Connections, which discusses therapeutic relationships; Developing a Sense of Self Through the Therapeutic Processes, which identifies stages of developmental recovery; Therapeutic Lights and Black Holes in the Shadows of child sexual abuse, which reflects on how a history of child sexual abuse influenced experiences of therapy; and Healing or Harrowing: Connecting With Others and First-time Experiences, which explores what was helpful, hindering, and new throughout the therapeutic journey. Findings related to participants developing new options for interpersonal relationships through the experience of authentic trust and the experiential learning of control and choice. Recommendations are discussed in relation to developing therapeutic practice and future research.